Model of a Work Breakdown Structure (WBS) Framework and AOA Diagram for Efficient Project Management of Lead â Zinc Skarn Exploration with Exploratory Data - Elham Ghadiri Soufi; Saeed Soltani Mohammadi; Hadi Mokhtari (مجله مدل سازی در مهندسی, 2018)
During recent years, investment in mineral resources exploration projects has been significantly growth in Iran. Since the implementation and completion of exploration projects require effort, long time and high cost as well as project managers technical capability, management techniques such as work breakdown structure in mineral exploration can prevent of wasting time and costs on these exploration. Skarn deposits exploration projects, as an important source of iron, copper, gold, lead and zinc, include major exploration projects. Skarn deposits are one of the most widespread types of deposits in the earth's crust and has been the subject of many studies over the centuries. Today, using of various techniques and methods of exploration can be these deposits more carefully studied, assessment and explored. In this paper, have been tried to used of  project management knowledge and  work breakdown structure, a appropriate model to perform the early stages of exploration of  lead – zinc skarn and finally combining the results in the GIS environment for mineral potential mapping in Mahneshan area be provided.